Approval in Nanotechnology Patents: Micro and Macro Factors That Affect Reactions to Category Blending - Lo, Jade Yu-Chieh; Kennedy, Mark Thomas (Organization Science, 2015)
Studies show that blending multiple categories rather than fitting one category cleanly undermines the appeal of market offerings, but in science and technology, blending multiple categories has been a formula for creating important new categories like nanotechnology. What enables such blends to earn approval and become recognized as new categories? We argue that reactions to category blending are affected by both micro and macro factors. Specifically, blend reactions are affected at the micro level by cognitive limits, especially as blends are repeated, and at the macro level by domain-specific logics for judging quality. Using data on nanotechnology patents, we test this argument by analyzing two dimensions of approval: time to approval and citations by subsequent patents. In addition to showing that blending has different effects on these two dimensions of approval, our findings suggest that reactions to blending are moderated, as argued, by (1) institutional logics that value novel combinations and (2) the repetition of blends that came to define nanotechnology. Our study contributes to theory by linking approval of category blends to cognitive limitations and cultural and institutional logics of evaluation.